Impact of diet on gastrointestinal health in adults with Gastroesophageal Reflux (GER) (Research, Society and Development, 2025)
Gastroesophageal reflux (GER) is a common condition affecting numerous individuals worldwide, characterized by the backward flow of stomach contents into the esophagus, generating symptoms such as heartburn, regurgitation, and chest discomfort. Diet plays a crucial role in modulating the symptoms of this condition, potentially either worsening or attenuating its clinical manifestations. The objective of this study was to investigate how certain foods and dietary patterns can impact the improvement or worsening of gastroesophageal reflux symptoms in adults. This is a narrative review of the scientific literature, conducted through consultation of PubMed, SciELO, and Google Scholar databases, using specific descriptors related to gastroesophageal reflux, nutrition, and diet therapy. Articles published preferably in the last ten years, in Portuguese and English, were analyzed, also including some studies from previous years that were considered relevant. The results demonstrated that simple carbohydrates, foods with high glycemic load, acidic and citrus products, as well as diets rich in FODMAPs, are associated with worsening GER symptoms. It is concluded that the nutritional approach is an essential therapeutic tool in GER management, and food and nutritional education, combined with understanding the pathophysiological mechanisms involved in this condition, allows optimizing symptom control and preventing complications, contributing significantly to improving the quality of life of patients with GER.